Philippines: The role of the legislature and legislators in advancing the cause of peace in Mindanao - Guioguio, Miguel V. (Animo Repository, 2005)
The current Mindanao conflict in the Philippines traces its roots to long-standing inter-cultural conflicts that have affected the island for centuries. The island's two major insurgent groups, the Moro National Liberation Front and the Moro Islamic Liberation Front have battled government troops over the last four decades with the aim of seceding from the Republic of the Philippines. This has caused untold sufferings to the island's inhabitants in terms of lost lives and human potential, socio-economic and cultural displacement, and delayed development of conflict-affected local communities and of the island in general. The government signed a peace pact with the MNLF in 1996 and is widely expected to complete peace negotiations with the MILF within 2005. This paper adopts the elements of the OPAPP's definition of a "Comprehensive Peace Process" in analyzing the legislature's role in the advancement of Mindanao peace. The OPAPP definition broadly covers various activities that seek to ensure a more sustainable peace. Taking into account the requirements of economic development, social justice and continuing political engagement, OPAPP identified six areas of concern in peace building (dubbed Six Paths to Peace or SPP), namely: 1) Pursuit of social, economic and political reforms; 2) Consensus-building and empowerment for peace; 3) Peace negotiations; 4) Reintegration and rehabilitation of former rebels; 5) Addressing concerns arising from continuing armed hostilities/assistance to communities affected by armed conflict; and 6) Nurturing and building a climate for peace. The paper then scans available information with respect to contributions by the Congress as an institution, and by Congressman and Senators as individual leaders, in promoting the government's peace-related initiatives in relation to the SPP. The paper uses this methodology to analyze such interventions and further identify other strategic areas and approaches for strengthening the role of parliaments in reducing conflict situations and sustaining peace with the country. Such analysis intends to also inform and support future international assistance, which has generally not been provided in this crucial field. The passage of Republic Act 6734 in 1989 which is entitled "The Organic Act for the Autonomous Region of Muslim Mindanao" is considered among the most important legislative outputs of the Philippine Congress relative to the Mindanao peace process. It was subsequently amended in 2001 by RA 9054 entitled "An act to Strengthen and Expand the Organic Act for the Autonomous Region in Muslim Mindanao," taking into account the suggestions made during the GRP-MNLF peace negotiations, albeit belatedly. Despite being an indirect prayer, a legislator has a range of opportunities to contribute to the peace process. Apart from lawmaking, the legislator can assert his/her leadership and influence by way of formal and non-formal peace advocacy- (both at the national and local levels) - and though the delivery of peace-enhancing projects, especially those funded by Congressional entitlements meant for constituencies. The study shows, however, that over the years, many legislators have been passive players in the peace process, allowing the executive to take the dominant role. Based on records, initiators of the peace-enhancing activities are mostly the legislative representatives of the Mindanao Island. The ideal situation is that all legislators in unison are supporting the peace initiatives. Legislators can still expand their role in the peace process beyond their inherent lawmaking powers. They can help plan program, implement, and monitor the various government efforts in enhancing the peace process. The broad concerns of the OPAPP's "Six Paths to Peace" demands great sensitivity from policy makers and legislators as well as continuing community inter-actions with political leaders. The proposed piloting of formal Participatory Planning in the congressional districts of Muslim Mindanao is expected to help the legislature respond to the needs of peace and development in a timely, rational, and cost-effective manner. The concept of Participatory Governance implemented through a proposed Participatory Planning and Oversight project can greatly contribute to good governance and, consequently, to a more lasting and sustainable peace process. This is especially true when constituents are engaged on a regular basis to help not only in giving insights to the ranking of policy priorities but also in hte monitoring of government projects and in the legislative oversight process. However, the proposal presumes unrealistically that: (1) constituents from Muslim Mindanao communities already have good exposure to democratic processes and have the confidence to engage their leaders in policy dialogues; (2) they have a reasonable understanding of the policy and developmental issues within their communities; and (3) they have well-developed communications channels within the local communities. In order to realize these conditions, there is need for external assistance towards capacity building in Muslim communities and establishing a public information and communications support system for grassroots organizations, local CSO's, and NGO's in the concerned communities.